Evaluation of the use of L-carnosine in short-term storage of ram semen with spermatological and flow-cytometric analyzes - Güngör, İH and Gür, S and Koca, RH and Çakır Cihangiroğlu, A and Güler Ekmen, E and Acısu, TC and Badıllı, N and Özer Kaya, Ş and Yüce, A and Sönmez, M and Türk, G (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was conducted to investigate the effect of adding different doses of L-carnosine to semen in vitro on the short-term storage of semen. Semen taken from 6 Akkaraman rams was used in the research. Semen taken from each animal was pooled. It was diluted with tris+egg yolk extender containing L-carnosine at different doses (1, 5, 10, 20, 50, 100 and 200 mM) and stored at +4°C for 96 hours. It was determined that 1, 5, 10, 20 mM L-carnosine doses increased total, progressive and rapid motility, kinematic parameters VCL, VSL, VAP values and high mitochondrial membrane potential level during short-term storage. It was also determined that these doses protected membrane integrity, reduced the rate of abnormal spermatozoon, acrosomal damage and low mitochondrial membrane potential level. It was determined that a dose of 200 mM L-carnosine had a toxic effect and negatively affected the parameters. As a result, when ram semen is desired to be stored for a short time (for 96 hours), it may be recommended to add 1, 5, 10 and 20 mM L-carnosine amino acid to the semen extenders in order to preserve spermatological parameters.